Ursolic and Oleanolic Acids as Potential Anticancer Agents Acting in the Gastrointestinal Tract - Pięt, Mateusz; Paduch, Roman (Mini-Reviews in Organic Chemistry, 2019)
Background: Cancer is one of the main causes of death worldwide. Contemporary therapies, including chemo- and radiotherapy, are burdened with severe side effects. Thus, there exists an urgent need to develop therapies that would be less devastating to the patient's body. Such novel approaches can be based on the anti-tumorigenic activity of particular compounds or may involve sensitizing cells to chemotherapy and radiotherapy or reducing the side-effects of regular treatment. Objective: Natural-derived compounds are becoming more and more popular in cancer research. Examples of such substances are Ursolic Acid (UA) and Oleanolic Acid (OA), plant-derived pentacyclic triterpenoids which possess numerous beneficial properties, including anti-tumorigenic activity. Results: In recent years, ursolic and oleanolic acids have been demonstrated to exert a range of anticancer effects on various types of tumors. These compounds inhibit the viability and proliferation of cancer cells, prevent their migration and metastasis and induce their apoptosis. Both in vitro and in vivo studies indicate that UA and OA are promising anti-cancer agents that can prevent carcinogenesis at each step. Furthermore, cancers at all stages are susceptible to the activity of these compounds. Neoplasms that are formed in the gastrointestinal tract, i.e. gastric, colorectal, pancreatic, and liver cancers, are among the most common and most lethal malignancies. Their localization in the digestive system, however, facilitates the action of orally-administered (potential) anti-cancer agents, making chemopreventive drugs more accessible. Conclusion: In this paper, the anti-tumorigenic effect of ursolic and oleanolic acids on gastric, colon, pancreatic, and liver cancers, as well as the mechanisms underlying this process, are presented.
Keywords: oleanolic acid